Reflux oesophagitis and oesophageal transit: evidence for a primary oesophageal motor disorder. Issue 4 (April 1988) - Eriksen, C A; Sadek, S A; Cranford, C; Sutton, D; Kennedy, N; Cuschieri, A
Abstract : Patients with reflux oesophagitis have a diminished capacity for distal oesophageal clearance. This is considered to be secondary to acid reflux damage to the oesophageal wall. We have postulated that the observed oesophageal dysmotility is a primary phenomenon. Using 24 hour oesophageal pH monitoring and the solid bolus oesophageal egg transit test, we evaluated the oesophageal transit of 55 patients, with symptomatic reflux oesophagitis, and 16 healthy volunteers. The transit for the entire oesophagus was significantly prolonged in the patient group. This delay was evident in all three segments of the oesophagus. Amongst the patients, there was significant correlation between the oesophageal transit time and the number of prolonged reflux events. No correlation was found, however, between symptom score or severity of endoscopic oesophagitis and transit time. These results would indicate that the oesophageal dysmotility is an integral part of gastrooesophageal reflux disease, and is more of a cause than an effect.